2015
DOI: 10.11646/zootaxa.4040.5.7
|View full text |Cite
|
Sign up to set email alerts
|

Parambassis serrata, a new species of glassperch (Teleostei: Ambassidae) from the Kaladan drainage, India

Abstract: Parambassis serrata, a new species of glassperch from the Kolo River, Kaladan drainage, Mizoram, India is described. It is distinguished from its congeners by the combination of characters that includes: presence of a faint, vertically-elongated brown humeral blotch; posterior margin of most spines of first dorsal fin proximally blackish; 14-16 dorsal and anal-fin branched rays; a black longitudinal stripe on ventral surface of caudal peduncle; absence of predorsal scales; a serrated preopercular ridge; 51-56 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…All the species of fishes belonging to Parambassis are strictly freshwater inhabitants and widely distributed in the Indian subcontinent mainland, peninsular Southeast Asia and the Australian region including New Guinea [11] and their numbers seem to be as many as 12 in Asia [12]. In India, Vishwanath et al [13] reported the presence of four ambassids from northeastern India (Chanda nama, Parambassis baculis, P. lala and P. ranga) while three more species were added (Parambassis bistigmata Geetakumari, [1]; P. waikhomi Geetakumari and Basudha [2], P. serrata Mayanglambam and Vishwanath, [14] accounting a total seven species of glassfish in the northeastern India [13,14]. Parambassis waikhomi and P. serrata are the only species recently described from the Chindwin River system in Manipur and the Kaladan River system in Mizoram respectively.…”
Section: Discussionmentioning
confidence: 99%
“…All the species of fishes belonging to Parambassis are strictly freshwater inhabitants and widely distributed in the Indian subcontinent mainland, peninsular Southeast Asia and the Australian region including New Guinea [11] and their numbers seem to be as many as 12 in Asia [12]. In India, Vishwanath et al [13] reported the presence of four ambassids from northeastern India (Chanda nama, Parambassis baculis, P. lala and P. ranga) while three more species were added (Parambassis bistigmata Geetakumari, [1]; P. waikhomi Geetakumari and Basudha [2], P. serrata Mayanglambam and Vishwanath, [14] accounting a total seven species of glassfish in the northeastern India [13,14]. Parambassis waikhomi and P. serrata are the only species recently described from the Chindwin River system in Manipur and the Kaladan River system in Mizoram respectively.…”
Section: Discussionmentioning
confidence: 99%